2020
DOI: 10.3390/agriculture10100440
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts and Attitudes of Agricultural Enterprises for Environmental Protection and Sustainable Development

Abstract: Recognising that implementing an agricultural enterprise impacts the state of the environment, its ecological stability, and the self- regulatory capabilities of ecosystems, the aim of this paper is to acquaint the professional and lay public about the attitudes of Slovakian agricultural enterprises towards environmental protection and sustainable development. The paper draws attention to present methods, techniques, and tools that enterprise management are applying for the purpose of meeting and overcoming en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…These factors should be further embedded in strategies developed by agricultural companies that can manage to sustain the total assets of the companies. On the other hand, based on the concerns/risks that were evidenced by negative implications of ESG measures on the total assets of agricultural companies, we propose the following strategies and policies for the agricultural companies: readjustment measures for reflected in targets set for CO 2 emissions, in agreement with CSR actions for environmental protection, as Juríčková et al [2] also underlined for agricultural companies from Slovakia; adapting the policies for resources mitigation, given the role of agriculture in consumption and supply of resources with many controversies that arise, according also to Carlson et al [1] and Juríčková et al [2]; stating CSR reporting regulations by the policymakers "about what items should be disclosed in the annual report (...) increasing the extent of CSR reporting should be done", as Ika et al [29] (p. 6) also highlighted for agriculture companies from Indonesia, jointly with widely applying the digital innovations for better transparency of CSR reporting, as Pirtea et al [7] also mentioned; using policies for a better governance of the agricultural companies setting targets for diversity and opportunity, but also policies for bribery and corruption; the effectiveness of the size of the board, considering the corporation model that may "have the highest asset, sales, and employee growth" [31] (p. 20); taking into consideration the inclusion of women on the board, being revealed that the presence of women on the board could influence "better decision making process, different attitude toward risk and more diversified skills used" [32] (p. 16); increasing the turnover of employees by applying technological innovations, with the implications also on the financial performance of the companies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors should be further embedded in strategies developed by agricultural companies that can manage to sustain the total assets of the companies. On the other hand, based on the concerns/risks that were evidenced by negative implications of ESG measures on the total assets of agricultural companies, we propose the following strategies and policies for the agricultural companies: readjustment measures for reflected in targets set for CO 2 emissions, in agreement with CSR actions for environmental protection, as Juríčková et al [2] also underlined for agricultural companies from Slovakia; adapting the policies for resources mitigation, given the role of agriculture in consumption and supply of resources with many controversies that arise, according also to Carlson et al [1] and Juríčková et al [2]; stating CSR reporting regulations by the policymakers "about what items should be disclosed in the annual report (...) increasing the extent of CSR reporting should be done", as Ika et al [29] (p. 6) also highlighted for agriculture companies from Indonesia, jointly with widely applying the digital innovations for better transparency of CSR reporting, as Pirtea et al [7] also mentioned; using policies for a better governance of the agricultural companies setting targets for diversity and opportunity, but also policies for bribery and corruption; the effectiveness of the size of the board, considering the corporation model that may "have the highest asset, sales, and employee growth" [31] (p. 20); taking into consideration the inclusion of women on the board, being revealed that the presence of women on the board could influence "better decision making process, different attitude toward risk and more diversified skills used" [32] (p. 16); increasing the turnover of employees by applying technological innovations, with the implications also on the financial performance of the companies.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity that arises between the resources used in agriculture (mainly natural resources, such as water, oil, coal, natural gas, pasture, etc.) and the products generated by the agricultural sectors (food, textiles, leather goods, and others) leads to several controversies regarding sustainable resource management and environment protection [1,2]. On the one hand, the use of natural resources brings to their decrease, which leads to solutions that ensure their sustainability, and, on the other hand, through the consumption of fossil fuels (as coal, crude oil, and natural gas), it brings a degradation of the environment by increasing CO 2 emissions into the atmosphere [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…To undertake environmental responsibility, enterprises need to make use of relevant theories in environmental economics, such as the environmental assessment method, environmental cost-benefit analysis, and economic analysis of environmental protection, to make decisions that are beneficial to both enterprises and the environment to achieve a win-win situation between enterprises and environmental protection. Juríčková et al (2020) showed that the corporate approach to environmental protection is essential to promote corporate sustainable development. Some scholars consider corporate investment in environmental protection as social investment, and studies have shown that corporate investment in environmental protection improves corporate efficiency and enhances corporate sustainability (Zheng et al, 2022).…”
Section: Enterprise Environmental Protection and Sustainable Developm...mentioning
confidence: 99%
“…Education for the growth and expansion of ecological services with new technologies aimed at farmers and beekeepers. Beside these support measures, there is a need to develop support programs for the parties involved in organic agriculture and beekeeping and the ability to understand the legislation; in addition, according to some authors [2] organic agriculture as a "sustainable" agricultural system offers a potential solution for sustaining biodiversity by helping to protect the environment.…”
Section: Melliferous Plain Vegetationmentioning
confidence: 99%